City and space: a hermeneutic perspective - Serna Castro, Yobany (Perseitas, 2024)
This paper presents a philosophical reflection on the city and the space. It proposes a different interpretation of the city, shifting the traditional focus on the historical and time-related aspects to a consideration of the space as a central category of analysis. This perspective seeks to define what a city is and to understand the different dynamics and processes that influence its constitution, development, transformation, or disappearance. In contrast to the traditional approach focused on the city with a temporal perspective, this paper highlights the relevance of the space as a fundamental element of analysis. The central premise lies in presenting an interpretation that highlights how the existence of the city is not only based on the processes of construction but also on the very act of inhabiting. This act, cemented by our relations with space, enables the existence of spatiality.